Species : new interdisciplinary essays - Wilson, Robert A. (Robert Andrew) (Bradford Book Ser., 1999)
This fresh collection of essays, drawn from a broad range of disciplines, brings neglected cognitive, anthropological, and historical dimensions to philosophical debates over species.